Predicting cycling performance in trained to elite male and female cyclists - Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2014)
In high-performance cycling, it is important to maintain a healthy balance between training load and recovery. Recently a new submaximal cycle test, known as the Lamberts and Lambert Submaximal Cycle Test (LSCT), has been shown to be able to accurately predict cycling performance in 15 well-trained cyclists. The aim of this study was to determine the predictive value of the LSCT in 102 trained to elite cyclists (82 men and 20 women). All cyclists performed an LSCT test followed by a peak-power-output (PPO) test, which included respiratory-gas analysis for the determination of maximal oxygen consumption (VO2max). They then performed the LSCT test followed by a 40-km time trial (TT) 72 h later. Average power output during the 3 stages of the LSCT increased from 31%, 60%, and 79% of PPO, while the ratings of perceived exertion increased from 8 to 13 to 16. Very good relationships were found between actual and LSCT-predicted PPO (r = .98, 95%CI: .97-.98, P < .0001), VO2max (r = .96, 95%CI: .97-.99, P < .0001) and 40-km-TT time (r = .98, 95%CI: .94-.97, P < .0001). No gender differences were found when predicting cycling performance from the LSCT (P = .95). The findings of this study show that the LSCT is able to accurately predict cycling performance in trained to elite male and female cyclists and potentially can be used to prescribe and fine-tune training prescription in cycling.